Determination of Fracture Paramaters of Effective Crack Model by Wedge-Splitting Test - Bildik, A. Tevfik; İnce, Ragıp (Fırat University, 2018)
Although the cracked beams have been widely utilized in fracture mechanics of concrete, there have been some advantages of the cubical/cylindrical specimens such as compactness and lightness. In the present work, the wedge-split-tension tests on cubical specimens with different cement contents and water/cement ratios were initially performed for the effective crack model. Finally, some relationships based on regression between the fracture parameters and the strength properties of concrete were derived. The results of the split-tension cube tests look viable and very promising.
Keywords: Engineering; Mühendislik